PENGAWETAN DUA JENIS KAYU IRIAN JAYA MEMAKAI BAHAN PENGAWET KOPPER FORMULA 7 SECARA RENDEMAN DINGIN - Sasa Abdurrohim; R Endahwati; S B Husodo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The penetration of wood preservative of ten wood species from Lampung was studied. The obaervation was conduct- ed afier the timber had been preserved by diffusion method. The BFCA 30% and wood •mples of 6 cm by 10 cm by 200 cm were used in this experiment.The results showed that wood .species haB significant effect on penetration, whi'le duration of di/fusion storage period haB the mme effect only on keruing, damar a8Clm, balam and cengal banglai.Eight weeks of storage was better than 4 weeks on those timber,. but not for the other species. According to IUFRO clasBifieation,pulai. kayu tabu and bintangur can be clasBifiedas permeable, while the others were classified aB moderate